Energy Drink before Exercise Did Not Affect Autonomic Recovery Following Moderate Aerobic Exercise: A Crossover, Randomized and Controlled Trial. (3rd April 2021) - Porto, Andrey Alves; Valenti, Vitor E.; Tonon do Amaral, Joice Anaize; Benjamim, Cicero Jonas R.; Garner, David M.; Ferreira, Celso
Abstract: Introduction: Energy drink (ED) intake could initiate physiological changes owing to its stimulant characteristics and, it improves endurance and athletic performance. We evaluated the acute effects of ED on autonomic heart rate (HR) control during recovery after a session of submaximal aerobic exercise. Method: The study was completed by submitting 29 healthy males between 18 and 30 years old to three conventions: (A) Maximum exercise test by the adapted Bruce protocol; (B) Placebo protocol (PP) - water intake 15 minutes prior to exercise, rest in dorsal decubitus for 15 minutes followed by 5 minutes of treadmill running at 1% inclination, initial speed of 5 km/h for 5 minutes 25 minutes with 60% of the velocity consistent to the maximum oxygen consumption (VO2max), and finally 60 minutes of recovery at rest in the supine position; (C) Experimental protocol (PE) - similar to PP previously, but with ED intake 15 minutes before physical exercise. The time, frequency and geometric indexes of HR variability (HRV) were inspected before and after exercise. Results: There was a significant (p < 0.05, <5%) effect on the HRV index (HR-nu and ms 2, LF-nu and ms 2, LF/HF, SD1, SDNN and RMSSD), indicating a reduction in HRV in the first 5 minutes after exercise in both protocols (PP and PE). Yet, no protocol interaction was detected, suggesting no effect of ED on HRV throughout recovery after submaximal aerobic exercise. Conclusion: There was no significant effect of ED on the autonomic control of HR in the recovery phase after submaximal aerobic exercise.